Working the Spaces of Neoliberalism 2005
DOI: 10.1002/9781444397437.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Dropping out or Signing up? The Professionalisation of Youth Travel

Abstract: Leaving school and dropping out of employment or further education was once an act of rebellion by cohorts of young people expressing anti-establishment sentiments. Now it has become a neoliberal market place in the UK. Over the last five years the ''gap year'' has changed from a radical activity, dominated by charities and inspired by the travel of the hippie generation, to an institutionally accepted commercial gap year industry which helps form new citizens for a global age. This transformation has seen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 9 publications
3
45
0
2
Order By: Relevance
“…Year each year; a figure based on official statistics concerning deferred entry into Higher Whatever the exact figure, previous academic studies of the Gap Year have generally concluded that it is an exclusive, class-bound phenomenon that perpetuates distinctions (Jones 2004, Simpson 2005, Heath 2007. Using data from Gap Year provider organisations, Jones (2004) has argued that gap year takers or 'gappers' are overwhelmingly middle-class, white, mostly female and from Southern England.…”
Section: Positioning the Gap Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Year each year; a figure based on official statistics concerning deferred entry into Higher Whatever the exact figure, previous academic studies of the Gap Year have generally concluded that it is an exclusive, class-bound phenomenon that perpetuates distinctions (Jones 2004, Simpson 2005, Heath 2007. Using data from Gap Year provider organisations, Jones (2004) has argued that gap year takers or 'gappers' are overwhelmingly middle-class, white, mostly female and from Southern England.…”
Section: Positioning the Gap Yearmentioning
confidence: 99%
“…Previous research has tended to focus on the Gap Year either as a form of social class positioning (Simpson 2005, Heath 2007 or a forum for undertaking transformations in identity during early adulthood (Beames 2004, Bagnoli 2009). This paper considers these two approaches, but argues that there is another possibility: that accounts of Gap Year experiences are used by young people to undertake forms of identity work within the context of Higher Education itself.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on the value of mobility for such outcomes is rather unconvincing and questions remain whether the skills acquired via cross border volunteering are indeed unattainable via more local volunteering or on the extent the contributions of cross-border volunteers are indeed needed and ethically minded. (Kristensen, 2004;Simpson, 2003;Thomas, 2001). All things considered, mobility remains one of the most appealing values of our times and a 'central policy concept' (Lindgren, 2010, p. 37).…”
Section: Previous Research On Barriers To Volunteeringmentioning
confidence: 99%
“…The selection process required that all participants had either resigned from their job or accepted a temporary career-break offer from their employer to travel abroad for a period of at least three months and undertake some form of culturally engaging activity, such as backpacking, volunteering or working. These criteria distinguish the typical career-break experience from the more generic vacation (Department for Education and Skills, 2004;Direct Line, 2006;Travelex;Simpson, 2005), targeting the former and eliminating the latter from investigation.…”
Section: Participantsmentioning
confidence: 99%
“…30-55 year olds are now more than twice as likely to take time out to travel than 18-24 year olds (Travelex, 2009), a pattern that is predicted to steadily increase (Mintel, 2008). This trend is reflected within the travel sector, as travel company Gap Year For Grown Ups (the UK's leading gap year provider), whose client base comprises 61% in the 25-50 year age bracket compared to 12% aged under 25, has seen 300% growth since 2005(Real Travel Group, 2010.…”
Section: Introductionmentioning
confidence: 99%